Implikasi Pembelajaran Zakat terhadap Pendidikan Sosial - M. Khairul Amri; Rachmat Panca Putera (Departement of Mathematics Education, 2024)
Education is a system and way to improve the quality of human life in all aspects of life. Education is a conscious effort needed to prepare humans to support their roles in the future, both as individual and social creatures. In relation to social life, the aim of education is directed at the formation of social human beings who have piety as the basis of attitudes and behavior. And it is directed towards the formation of humans who have an awareness of obligations, rights and social responsibilities, as well as a tolerant attitude, so that harmonious relationships between fellow humans can run harmoniously. The research design used in this research is a qualitative type of research. In this research the author used library research. To analyze the data in this research the author used interpretative methods and content analysis. Based on data analysis in this research, the author can conclude that zakat is one method in the process of forming social attitudes that needs to be instilled and fostered in forming Muslim individuals. Through direct practice methods (coaching) in everyday life. So zakat will become part of the actions and behavior of human life